Amotosalen/UVA treatment inactivates T cells more effectively than the recommended gamma dose for prevention of transfusion‐associated graft‐versus‐host disease. Issue 6 (2nd April 2018) - Castro, Grace; Merkel, Patricia A.; Giclas, Hannah E.; Gibula, Andrew; Andersen, Gillian E.; Corash, Laurence M.; Lin, Jin Sying; Green, Jennifer; Knight, Vijaya; Stassinopoulos, Adonis
Abstract : INTRODUCTION: Transfusion‐associated graft‐versus‐host disease (TA‐GVHD) is a rare complication after transfusion of components containing viable donor T cells. Gamma irradiation with doses that stop T‐cell proliferation is the predominant method to prevent TA‐GVHD. Treatment with pathogen inactivation methodologies has been found to also be effective against proliferating white blood cells, including T cells. In this study, T‐cell inactivation was compared, between amotosalen/ultraviolet A (UVA) treatment and gamma‐irradiation (2500 cGy), using a sensitive limiting dilution assay (LDA) with an enhanced dynamic range. METHODS AND MATERIALS: Matched plasma units (N = 8), contaminated with 1 × 10 6 peripheral blood mononuclear cells (PBMCs) per mL, were either treated with amotosalen/UVA or gamma irradiation, or retained as untreated control. Posttreatment, cells were cultured under standardized conditions. T‐cell proliferation was determined by the incorporation of 3 H‐thymidine and correlated with microscopic detection. RESULTS: Range‐finding experiments showed that after gamma irradiation (2500 cGy), significant T‐cell proliferation could be observed at a 1 × 10 7 cell culture density, some proliferation at 1 × 10 6, and none at 1 × 10 5 cells/well. Based on these facts, a quantitative comparison was carried out between amotosalen/UVA at the highest challenge of 1 × 10 7 PBMCs/well, and gamma irradiation at 1 × 10 6 and 1 × 10 5 PBMCs/well. Complete inactivation of the T cells after amotosalen/UVA treatment was observed, equivalent to greater than 6.2 log inactivation. Complete inactivation of the T cells was also observed after gamma irradiation when 1 × 10 5 PBMCs/well were cultured (>4.2 log inactivation). Proliferation was observed when 1 × 10 6 PBMCs/well were cultured (≤5.2 log inactivation) after gamma irradiation. CONCLUSION: Amotosalen/UVA treatment more effectively inactivates T cells than the current standard of gamma irradiation (2500 cGy) for the prevention of TA‐GVHD.